A PP2A‐mediated feedback mechanism controls Ca2+‐dependent NO synthesis under physiological oxygen. Issue 12 (31st July 2017) - Keeley, Thomas P.; Siow, Richard C. M.; Jacob, Ron; Mann, Giovanni E.
ABSTRACT: Intracellular O2 is a key regulator of NO signaling, yet most in vitro studies are conducted in atmospheric O2 levels, hyperoxic with respect to the physiologic milieu. We investigated NO signaling in endothelial cells cultured in physiologic (5%) O2 and stimulated with histamine or shear stress. Culture of cells in 5% O2 (>5 d) decreased histamine‐but not shear stress–stimulated endothelial (e)NOS activity. Unlike cells adapted to a hypoxic environment (1% O2 ), those cultured in 5% O2 still mobilized sufficient Ca 2+ to activate AMPK. Enhanced expression and membrane targeting of PP2A‐C was observed in 5% O2, resulting in greater interaction with eNOS in response to histamine. Moreover, increased dephosphorylation of eNOS in 5% O2 was Ca 2+ ‐sensitive and reversed by okadaic acid or PP2A‐C siRNA. The present findings establish that Ca 2+ mobilization stimulates both NO synthesis and PP2A‐mediated eNOS dephosphorylation, thus constituting a novel negative feedback mechanism regulating eNOS activity not present in response to shear stress. This, coupled with enhanced NO bioavailability, underpins differences in NO signaling induced by inflammatory and physiologic stimuli that are apparent only in physiologic O2 levels. Furthermore, an explicit delineation between physiologic normoxia and genuine hypoxia is defined here, with implications for our understanding of pathophysiological hypoxia.—Keeley, T. P., Siow, R. C. M., Jacob, R., Mann, G. E. A PP2A‐mediated feedback mechanism controls Ca 2 +‐dependent NO synthesis under physiological oxygen. FASEB J. 31, 5172–5183 (2017). www.fasebj.org